Efektivitas Manajemen Risiko pada Bank Syariah dan Konvensional: Studi Komparatif - M. Masrukhan; Tessa Arismah Palar; Revina Permata Auli; Rahma Rizqyna Nur Fazri (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
This research aims to determine the effectiveness of risk management in Islamic banks and conventional banks in Indonesia through a comparative approach. Risk management is an important aspect in the banking industry to mitigate credit, market and liquidity risks that affect financial stability and customer trust. Using qualitative methods based on literature study, this research analyzes related secondary data. The research results show that Islamic banks are more resilient to market risks due to derivative transactions, but face problems in management due to limited liquidity of liquid sharia instruments. In contrast, conventional banks have an advantage in managing liquidity risk with wider access to money market instruments. These findings are expected to provide input for regulators and practitioners in designing risk management strategies that are effective and appropriate to the operational characteristics of both types of banks. Analysis of the effectiveness of risk management in Islamic and conventional banks in Indonesia using a comparative approach. This qualitative research uses literature study with secondary data. The results show that Islamic banks are more resilient to market risk but face liquidity constraints, while conventional banks are stronger in liquidity risk management thanks to wider access to money market instruments. These findings are expected to help regulators and practitioners in developing effective risk management strategies according to the characteristics of each bank.